First records of metal concentrations in the Pacific oyster (Crassostrea gigas) from a Southwest Atlantic estuary - la Colla, Noelia Soledad; Botté, Sandra Elizabeth; Fiori, Sandra Marcela; Dos Santos, Eder Paulo; Labudía, Ana Carolina (Environmental Geochemistry and Health)
The Pacific oyster (Crassostrea gigas) is one of the world’s most widespread bivalves and a suitable species for biomonitoring metals in coastal environments. In the present research, wild individuals were collected from an Argentinian estuary and the coastal beaches nearby. The concentrations of eight metals (Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn) were quantified in the soft tissues of the Pacific oyster. Among the metals, Cu, Fe and Zn reached the highest concentrations in the soft tissues over the rest of the elements. The results showed the highest values to be estuary related, with the beach site achieving the lowest values. These results possibly lie on the impact of human activities surrounding the estuary, as well as streams and rivers that outflow within it. Higher Cu and Zn levels, both port related, were mainly found toward the outer estuary. On the other hand, high levels of Cr, Fe and Mn were found toward the inner zone of the estuary, an area with sewage sludge from the cities located on the margins of the BBE. Regarding the potential risk to public health, Cu and Zn levels found in C. gigas were above national and international safety guidelines in 100% and 11% of the samples, respectively. Fil: la Colla, Noelia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina Fil: Botté, Sandra Elizabeth. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina. Universidad Nacional del Sur. Departamento de Biología, Bioquímica y Farmacia; Argentina Fil: Fiori, Sandra Marcela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. ...